1968
DOI: 10.1139/m68-091
|View full text |Cite
|
Sign up to set email alerts
|

Some patterns of B vitamin requirements among neritic marine bacteria

Abstract: Twenty-four different patterns of single and multiple requirements for various B vitamins were demonstrated for 665 cultures of marine bacteria grown in a basal synthetic seawater medium enriched with phosphate, vitamin-free casamino acids, dextrose, and succinate. Among 114 thiamine-requiring isolates, 55 were unable to make the pyrimidine moiety, 19 required thiazole, 13 needed both thiazole and the pyrimidine moiety, while 27 organisms required thiamine o r thiamine pyrophosphate for growth. Among 142 bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

1969
1969
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
(9 reference statements)
0
14
1
Order By: Relevance
“…Presumably the remaining 2/3 of prokaryotes acquire extracellular cobalamin or have evolved B 12 -independent pathways (Rodionov et al 2003). Experimental and genetic evidence demonstrate that some prokaryotic taxa possess salvage pathways to assimilate extracellular B 12 or its precursors from their environment (Burkholder and Lewis 1968;Woodson and Escalante-Semerena 2004). Our first field experiment demonstrated that organisms in the 0.2-1.0-mm size class assimilated cobalamin roughly in proportion to their biomass and productivity ( Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Presumably the remaining 2/3 of prokaryotes acquire extracellular cobalamin or have evolved B 12 -independent pathways (Rodionov et al 2003). Experimental and genetic evidence demonstrate that some prokaryotic taxa possess salvage pathways to assimilate extracellular B 12 or its precursors from their environment (Burkholder and Lewis 1968;Woodson and Escalante-Semerena 2004). Our first field experiment demonstrated that organisms in the 0.2-1.0-mm size class assimilated cobalamin roughly in proportion to their biomass and productivity ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Within a Rhô ne estuary culture collection (n 5 232), for example, only 3.5%, 10%, and 14% of clones were truly auxotrophic for cobalamin, biotin, and thiamin, respectively, i.e., no growth without extracellular B vitamin (Berland et al 1976). In Burkholder and Lewis' (1968) collection (n 5 665) of B-vitamin auxotrophs isolated from temperate coastal waters and sediments, .20% of clones required extracellular cobalamin, either alone or combined with other B vitamins. We conclude that salvage pathways for B 12 assimilation were commonly expressed among bacteria at our site and that B 12 auxotrophy among marine prokaryotes is not rare.…”
Section: Resultsmentioning
confidence: 99%
“…B1 is intriguing with respect to bacterial ecology, as B1-prototrophic (de novo synthesizers of the vitamin) and B1-auxotrophic populations (those incapable of de novo B1 biosynthesis) occur in nature, with the latter lacking one or more core B1-biosynthesis genes and requiring exogenous B1 or B1 precursors to survive (1,4,5). Surveys of isolate growth or genomes indicate that most (∼70-80%) bacterial isolates from estuarine/marine waters are B1 prototrophs (4)(5)(6)(7). In notable contrast, isolates representing abundant marine and freshwater bacterioplankton lineages, such as the SAR11 and SAR86 clades and Actinobacteria, are B1 auxotrophs (8)(9)(10).…”
mentioning
confidence: 99%
“…Surveys of the occurrence of vitamin auxotrophy within phytoplankton noted that a large percentage ( 80%) of prymnesiophytes were B1 auxotrophs (Provasoli and Carlucci 1974;Croft et al 2006). In contrast, a majority of diatoms produce B1 (Provasoli and Carlucci 1974), and both B1 producing and auxotrophic bacteria are present in the ocean (MacLeod et al 1954;Burkholder and Lewis 1968).…”
mentioning
confidence: 99%